Apparent emissivity measurement of semi-transparent materials part 2: Theoretical concept. (January 2021) - Gieseler, Julian; Adibekyan, Albert; Monte, Christian; Hollandt, Jörg
Highlights: Emission, transmission, and reflection are intertwined for semitransparent materials. Low temperature IR emissivity measurement is complicated by large thermal background. Solution: Development of a new sample holder and evaluation scheme. Allows simultaneous identification of transmittance and reflectance. Sensitivity analysis of evaluation scheme performed. Abstract: Semi-transparent materials are increasingly applied in various industrial and scientific applications. Because there is a strong coupling between optical and thermal properties of these materials, they pose unique challenges for their modelling and experimental characterization. At PTB, the facilities for spectral emissivity measurement of opaque materials have been expanded for the characterization of semi-transparent materials in the near-, mid- and far-IR region and for temperatures between 20 °C and 90 °C by using a new sample holder. The experimental realization and validation of the new facility for emissivity measurement of semi-transparent materials is presented in part 1 of this publication. Here the evaluation procedure of the measurement data obtained with the new sample-holder is discussed in detail. A model of radiative transport within semi-transparent samples considering emission, absorption, scattering and multiple reflections was formulated and solved over a wide spectral range. The model was inverted using a least squares approach and an extensive sensitivity analysis was performed.